The 3c’s of change leadership: a brief outlook / Azfahanee Zakaria, Syed Mohammed Alhady Syed Ahmad Alhady and Sarah Sabir Ahmad - Zakaria, Azfahanee; Alhady, Syed Mohammed; Sabir Ahmad, Sarah (Universiti Teknologi MARA, Kedah, 2022)
The change in the business arena is drastic and rapid. Should an organization do not accept the change and move side by side with change, the organization will be left behind (McShane & Von Glinow, 2018). In order to stay competitive, organization need to keep pace with ongoing changes in the external environment such as the demand of customers, community expectation, global competition as well as technology advancement. Hence, succesful organization will act fast and plan strategically as to ensure that the organization is at par with other competitors as well. Nevertheless, all the changes and what strategy to implement will only be successful if the leader is receptive to change. Should the leader be a person who is complacent and not a risk taker, adapting and accepting changes would be a challenge. According to The Difference Between Change Management (n.d), change leadership’s style is a proactive approach towards change management. Change leaders view change as a stepping stone for growth and improvement. In leading, these leaders use people centric method whereby employees work process, tools and wellbeing are their top priority. Furthermore, according to Hole (2020), 70 percent of change programs were not successful and failed to achieve its goals due to reluctance from the employees to change and there was minimal management support.